1924
DOI: 10.1084/jem.40.4.543
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Interstitial Myocarditis in Rabbits

Abstract: The hearts of thirty-four apparently healthy adult rabbits were carefully studied microscopically. Twenty, or 60 per cent, contained lesions consisting of lymphocytes and endothelial leucocytes invarying proportions, to which were sometimes added polymorphonuclear eosinophils, plasma cells, and fibroblasts in small numbers. The lesions occurred most frequently between the muscle fibers of the papillary muscles and ventricular walls, and occasionally beneath the endocardium and epicardium. No microorganisms or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
3
0

Year Published

1938
1938
1964
1964

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(10 citation statements)
references
References 1 publication
7
3
0
Order By: Relevance
“…It should be noted that small foci of lymphocytes and monocytes, without associated muscle necrosis, as have been described by other investigators (27,28), were seen in most of the hearts from all the animals studied. The studies herein reported, like a number published previously from these and other laboratories (13)(14)(15), were designed to assay the effects of group A streptococcal infections on the hearts of rabbits.…”
Section: Control Studiessupporting
confidence: 80%
“…It should be noted that small foci of lymphocytes and monocytes, without associated muscle necrosis, as have been described by other investigators (27,28), were seen in most of the hearts from all the animals studied. The studies herein reported, like a number published previously from these and other laboratories (13)(14)(15), were designed to assay the effects of group A streptococcal infections on the hearts of rabbits.…”
Section: Control Studiessupporting
confidence: 80%
“…The interstitial myocarditis found in some of the rabbits during our experiments was unrelated to the injections and probably represented the spontaneous interstitial myocarditis sometimes encountered (11).…”
Section: Discussionsupporting
confidence: 52%
“…Cellular infiltrates were occasionally seen in the rabbits, but they were limited in extent and could not he ascribed to the hypothermia, because similar changes were also found in the control animals. Cellular infiltrates in the heart muscles from apparently healthy rabbits have also been demonstrated by Miller ( 9 ) and Mc Keown ( l o ) , for example.…”
Section: It E S I' I T S a N D D I S C I' S S I 0 H'supporting
confidence: 58%